Vitamin A or E and a catechin synergize as vaccine adjuvant to enhance immune responses in mice by induction of early interleukin‐15 but not interleukin‐1β responses. Issue 4 (22nd June 2016) - Patel, Sapna; Akalkotkar, Archana; Bivona, Joseph J.; Lee, Ji‐Young; Park, Young‐Ki; Yu, Mingke; Colpitts, Sara L.; Vajdy, Michael
Summary: Vitamins A and E and select flavonoids in the family of catechins are well‐defined small molecules that, if proven to possess immunomodulatory properties, hold promise as vaccine adjuvants and various therapies. In an effort to determine the in vivo immunomodulatory properties of these molecules, we found that although mucosal and systemic vaccinations with a recombinant HIV‐1BaL gp120 with either a catechin, epigallo catechin gallate (EGCG) or pro‐vitamin A (retinyl palmitate) alone in a vegetable‐oil‐in‐water emulsion (OWE) suppressed antigen‐specific responses, the combination of EGCG and vitamin A or E in OWE (Nutritive Immune‐enhancing Delivery System, NIDS) synergistically enhanced adaptive B‐cell, and CD4 + and CD8 + T‐cell responses, following induction of relatively low local and systemic innate tumour necrosis factor‐ α (TNF‐ α ), interleukin‐6 (IL‐6) and IL‐17, but relatively high levels of early systemic IL‐15 responses. For induction of adaptive interferon‐ γ and TNF‐ α responses by CD4 + and CD8 + T cells, the adjuvant effect of NIDS was dependent on both IL‐15 and its receptor. In addition, the anti‐oxidant activity of NIDS correlated positively with higher expression of the superoxide dismutase 1, an enzyme involved in reactive oxygen species elimination but negatively with secretion of IL‐1 β . This suggests that the mechanism of action of NIDS is dependent on anti‐oxidant activity and IL‐15, but independent of IL‐1 β and inflammasome formation. These data show that this approach in nutritive vaccine adjuvant design holds promise for the development of potentially safer effective vaccines.